CAKUT: A Pediatric and Evolutionary Perspective on the Leading Cause of CKD in Childhood - Robert L. Chevalier (MDPI AG, 2023)
The global prevalence of chronic kidney disease (CKD) is increasing rapidly, due to increasing environmental stressors through the life cycle. Congenital anomalies of kidney and urinary tract (CAKUT) account for most CKD in children, with a spectrum that can lead to kidney failure from early postnatal to late adult life. A stressed fetal environment can impair nephrogenesis, now recognized as a significant risk factor for the development of adult CKD. Congenital urinary tract obstruction is the leading cause of CKD due to CAKUT and can itself impair nephrogenesis as well as contribute to progressive nephron injury. Early diagnosis by ultrasonography in fetal life by an obstetrician/perinatologist can provide important information for guiding prognosis and future management. This review focuses on the critical role played by the pediatrician in providing timely evaluation and management of the patient from the moment of birth to the transfer to adult care. In addition to genetic factors, vulnerability of the kidney to CKD is a consequence of evolved modulation of nephron number in response to maternal signaling as well as to susceptibility of the nephron to hypoxic and oxidative injury. Future advances in the management of CAKUT will depend on improved biomarkers and imaging techniques.